Respuesta :

Answer:

x=5[tex]\frac{16}{3}[/tex]/(4-[tex]\frac{16}{3}[/tex])

Step-by-step explanation:

Hi, these are not my strong point, Sorry if its incorrect.

6-[tex]\frac{2}{3}[/tex](x+5)=4x

I first did 6-[tex]\frac{2}{3}[/tex]

6/1 -2/3,  18/3-2/3 =16/3

[tex]\frac{16}{3}[/tex](x+5)=4x

I then expanded the bracket to get [tex]\frac{16}{3}[/tex]x+5[tex]\frac{16}{3}[/tex]

[tex]\frac{16}{3}[/tex]x+5[tex]\frac{16}{3}[/tex]=4x

Then I took away [tex]\frac{16}{3}[/tex]x from both sides to get.

5[tex]\frac{16}{3}[/tex]=4x-[tex]\frac{16}{3}[/tex]x

I then factorised x out

5[tex]\frac{16}{3}[/tex]=x(4-[tex]\frac{16}{3}[/tex])

I then divided by the bracket to get:

x=5[tex]\frac{16}{3}[/tex]/(4-[tex]\frac{16}{3}[/tex])

Answer:

4/7

Step-by-step explanation:

[tex]6 - \frac{2}{3} (x + 5) = 4x[/tex]

U take -2/3 into the brackets

[tex]6 - \frac{2}{3} x - \frac{10}{3} = 4x[/tex]

Put all values with x on one side

[tex]6 - \frac{10}{3} = 4x + \frac{2}{3} x[/tex]

Ensure that they all have the same denominator so that u can add and subtract

[tex] \frac{18}{3} - \frac{10}{3} = \frac{12}{3} x + \frac{2}{3} x[/tex]

[tex] \frac{8}{3} = \frac{14}{3} x[/tex]

Drop the denominator since they both have the same denominator

[tex]8 = 14x[/tex]

divide both sides by 14

[tex] \frac{8}{14} = \frac{14}{14} x[/tex]

[tex]x = \frac{4}{7} [/tex]

ACCESS MORE